1992
DOI: 10.1002/nbm.1940050403
|View full text |Cite
|
Sign up to set email alerts
|

Application of time‐domain fitting in the quantification of in vivo1H spectroscopic imaging data sets

Abstract: Time-domain model function fitting techniques were applied to improve the reconstruction of metabolite maps from the data sets obtained from in vivo 1H spectroscopic imaging (SI) experiments. First, residual water-related signals were removed from the SI data sets by using SVD-based linear time-domain fitting based upon the HSVD (State Space) approach. Second, peak integrals of the metabolites of interest were obtained by quantifying the proton spin-echoes of the voxels by means of non-linear time-domain fitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 14 publications
0
57
0
Order By: Relevance
“…The methylene signal, which represents intracellular trigyceride, was measured at 1.4 ppm. The spectra were fitted in the time domain using the variable projection method (32,33). Spectroscopic intracellular triglyceride content (in percent) was expressed as a ratio of the area under the methylene peak to that under the sum of methylene and water peaks ϫ 100 (LFAT).…”
Section: Methodsmentioning
confidence: 99%
“…The methylene signal, which represents intracellular trigyceride, was measured at 1.4 ppm. The spectra were fitted in the time domain using the variable projection method (32,33). Spectroscopic intracellular triglyceride content (in percent) was expressed as a ratio of the area under the methylene peak to that under the sum of methylene and water peaks ϫ 100 (LFAT).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of resolved glucose resonances may be critical in achieving the needed accuracy for glucose measurements by 1 H NMR. Extensions to other deconvolution methods are possible, although it remains to be demonstrated that other quantification methods, e.g., time domain fitting with prior knowledge (21,62), principal component (22) or wavelet analysis (23), are able to handle such large sets of model spectra, containing multiple resonances, and that they are equally robust. It also remains to be shown whether the accuracy and efficiency of quantification of metabolites with low concentrations can be improved using alternate methods, which focus on the detection of selected metabolites, e.g., spectral editing of GABA (46) or using 2D fitting of multiple echo times (21).…”
Section: Quantificationmentioning
confidence: 99%
“…For the processing of metabolite spectra, the remaining water signal intensity was removed by using a HankelLanczos singular value decomposition filter, and amplitudes of Cho, Cr, and NAA signals were calculated with appropriate prior knowledge by using the advanced method for accurate, robust, and efficient spectral fitting. 22,23 The amplitude of water signal intensity for each processed voxel was assessed from the scan without water suppression.…”
Section: Mr Imaging and Mr Spectroscopymentioning
confidence: 99%